COMPORTAMENTOS DE TELA E SONO E SUAS CORRELAÇÕES COM O IMC EM CRIANÇAS DA PRIMEIRA INFÂNCIA - Claudio Henrique Pereira Verão (2024)
Introduction: Excessive time spent on digital devices and limited sleep duration are associated with impacts on children's physical and mental health, such as increased sedentary behaviors and the risk of obesity. Early childhood is a critical period for establishing healthy habits, and monitoring screen time and sleep is essential to prevent future health problems. Objective: To analyze the relationship between screen time, sleep duration, and body mass index (BMI) in young children. Methods: The study included 270 children aged 3 to 5 years, 138 females and 132 males. Weight and height were measured, as well as self-reported data from parents or caregivers on screen time and sleep duration. In the statistical analysis, the Shapiro-Wilk test was used to determine normality in relation to the data distribution. If there was no normality, nonparametric tests were used to compare means. The Mann-Whitney test was used to analyze differences between groups. The correlation between the main variables was performed using Spearman's correlation coefficient test. Results and Discussion: Boys had more screen time (178.3±94) than girls (162.2±99.4), but there was no significant difference in sleep time between the sexes (p>0.05). (OBS: Por falta de caracteres, verificar a dissertação original para ter acesso ao resumo.)